Moral harassment in the security forces: is it worrying? - Cerdeira Campos Costa, Sandra; S. Azevedo, Rui M.; Peixoto, Bruno; Madureira-Carvalho, Áurea (Scientific Letters, 2024)
Background: Moral Harassment is a set of continuous violent acts that cause psychological and/or physical harm to victims [1]. In Portugal, it was only in the 1990s that was considered, and it currently has a major impact on society, in public and private institutions [2, 3], which led to legislation, protecting victims and penalizing aggressors [4]. Objective: Obtain knowledge to identify, prevent, and reduce moral harassment within security forces. Methods: A questionnaire survey was created, consisting of 3 parts: i) sociodemographic data of the sample; ii) Leymann Inventory of Psychological Terrorization (LIPT-60) scale; iii) questions about moral harassment. The questionnaire was implemented in LimeSurvey and distributed by email to all members of the Associação dos Profissionais da Guarda and the Associação Sindical dos Profissionais da Polícia. Data was analyzed using descriptive statistics and IBM SPSS Statistics 29.0. Results: We obtained 302 complete answers (62 females; 240 males). The negative behaviors with the highest percentage (77.82%) are related to preventing self-expression, and the dimensional indicators with the highest average are the Job Demeaning Index (0.95) and the Express Intimidation Index (1.04). This instrument presents a very good reliability (Cronbach's alpha=0.9817). The characterization of the sample revealed that 96% had heard of moral harassment, 30.8% had been/were victims of the phenomenon, of which the majority were male (74.2%). 19.2% of the total participants considered that the violence they had suffered disrupted their work and performance. The main symptoms were difficulty falling asleep and insomnia, anxiety, anguish and sadness, and nervousness, and 17.2% of victims even mentioned ideas of homicide and/or suicide. Conclusions: A significant level of moral harassment is lived within the security forces, with laboral discredit and intimidation being the most prevalent forms. This is a worrying and emerging situation, and preventive measures need to be taken to avoid more severe consequences such as suicide.